1980
DOI: 10.1203/00006450-198014070-00007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Quantitation of a Zinc-Binding Ligand in Human Milk

Abstract: SummaryA low-molecular-weight zinc-binding ligand from human milk has been isolated and characterized. The ligand was isolated by chromatography on Dowex 50, Dowex 1, and Sephadex G-15 equilibrated with 0.153 mM Zn(N03)2. Mass spectroscopy, thinlayer chromatography, and infrared spectroscopy proved that the zinc-binding ligand isolated by this method from human milk is pyridine-2-carboxylic acid, commonly known as picolinic acid. The concentration of picolinic acid in human milk was 308 pM, the concentration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

1983
1983
1997
1997

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
6
0
3
Order By: Relevance
“…The identity of this low molecular weight zincbinding ligand in human milk has been the subject of much controversy. Evans and Johnson (1980) suggested that picolinic acid is the ligand, but this has been discounted by Rebello et a/. (1983) who found that the concentration of picolinic acid in human milk is insufficient to bind a significant proportion of the zinc and by Hurley and Lonnerdal (1981) who found that picolinic acid does not bind zinc in human milk.…”
Section: Zincmentioning
confidence: 99%
“…The identity of this low molecular weight zincbinding ligand in human milk has been the subject of much controversy. Evans and Johnson (1980) suggested that picolinic acid is the ligand, but this has been discounted by Rebello et a/. (1983) who found that the concentration of picolinic acid in human milk is insufficient to bind a significant proportion of the zinc and by Hurley and Lonnerdal (1981) who found that picolinic acid does not bind zinc in human milk.…”
Section: Zincmentioning
confidence: 99%
“…Premature infants therefore have a considerable requirement for zinc. Although human milk contains less zinc than cow's milk, some of the zinc is associated with low molecular weight compounds picolinic acid (EVANS and JOHNSON 1980) or citrate, whereas it is entirely associated with high molecular weight compounds in cow's milk (COUSINS and SMITH 1980) from which zinc is less well absorbed by the neonatal gastrointestinal tract. Although human milk contains less zinc than cow's milk, some of the zinc is associated with low molecular weight compounds picolinic acid (EVANS and JOHNSON 1980) or citrate, whereas it is entirely associated with high molecular weight compounds in cow's milk (COUSINS and SMITH 1980) from which zinc is less well absorbed by the neonatal gastrointestinal tract.…”
Section: Chapter 33mentioning
confidence: 99%
“…Mit diesen Komplexeigenschaften dtirfte in Zusammenhang stehen, dab Krieger [20] die Zn-Dosis zur erfolgreichen Behandlung von Akrodermatitis enteropathica mit Zn-Dipikolinat im Vergleich zu einem Zn-Salz deutlich erniedrigen konnte. Die gleiche Arbeitsgruppe wies mit Hilfe der Isotopenverdiinnungsmethode ebenfalls nach, dab bereits durch die alleinige Zugabe yon 0,2 g Pikolins~iure pro kg Futter zuverschiedenen Rattendiiiten die Zn-Absorption signifikant gesteigert werden kann [5,6,7,9]. Die gleiche Arbeitsgruppe wies mit Hilfe der Isotopenverdiinnungsmethode ebenfalls nach, dab bereits durch die alleinige Zugabe yon 0,2 g Pikolins~iure pro kg Futter zuverschiedenen Rattendiiiten die Zn-Absorption signifikant gesteigert werden kann [5,6,7,9].…”
Section: Diskussionunclassified
“…Als Hypothese ffir die Absorption kann angenommen werden, dab durch organische Liganden als ,,niedermolekulare, Zn-bindende Komponenten" die Aufnahme yon Zink aus dem Darmlumen fiber den Bfirstensaum der Mukosazellen erleichtert und/oder der Transport durch die Absorptionszelle und der Durchtritt durch die basolaterale Zellmembran beeinflugt werden. ~ber die Konzentration von Pikolins~iure in einzelnen Organen oder in der Humanmilch liegen erst wenige, sehr unterschiedliche Ergebnisse vor [6,9,27]. Forth und Rummel [11] bezeichnen dies als eine Frage der effektiven Komplexstabilitiit.…”
Section: Tabelle 3 Zn-absorption In Vitro Nach Zugabe Yon Zink Mit Zunclassified
See 1 more Smart Citation